Patients in northwestern Turkey prefer herbs as complementary medicine after breast cancer diagnosis - GÜLLÜOĞLU, MAHMUT BAHADIR (KARGER, 2008)
Background: A cross-sectional survey was conducted in order to define the prevalence, pattern, and predictors of complementary and alternative medicine (CAM) use in breast cancer patients in northwestern Turkey. Patients and Methods: All patients admitted to the breast center between January 2005 and January 2006 were consecutively included in the study. Demographics and clinical data of study patients were noted. A 15-item questionnaire was used to document the attitude of breast cancer patients towards CAM modalities. Primary outcomes were prevalence, pattern, and predictors of CAM. Secondary outcomes were the reasons for CAM use, the number and type of adverse events related to CAM use, and the satisfaction level of CAM users. Results: Nearly one third of breast cancer patients use at least one type of CAM in addition to conventional therapy. Most chose herbal medicines which they think support their general health status. Nettle (Urtica diocia/U. urens) was the most common herbal medicine that patients consume. Previous experience with CAM was the most significant factor for CAM use after breast cancer diagnosis. Being young and married as well as receiving radiotherapy were among other independent factors for using any CAM modality.
Keywords: breast cancer; complementary medicine; supportive care; therapy; ALTERNATIVE MEDICINE; PREVALENCE; WOMEN; ONCOLOGY; THERAPIES